Dynamic changes in large-scale functional network organization during autobiographical memory retrieval. (February 2018) - Inman, Cory S.; James, G. Andrew; Vytal, Katherine; Hamann, Stephan
Abstract: Autobiographical memory (AM), episodic memory for life events, involves the orchestration of multiple dynamic cognitive processes, including memory access and subsequent elaboration. Previous neuroimaging studies have contrasted memory access and elaboration processes in terms of regional brain activation and connectivity within large, multi-region networks. Although interactions between key memory-related regions such as the hippocampus and prefrontal cortex (PFC) have been shown to play an important role in AM retrieval, it remains unclear how such connectivity between specific, individual regions involved in AM retrieval changes dynamically across the retrieval process and how these changes relate to broader memory networks throughout the whole brain. The present functional magnetic resonance imaging (fMRI) study sought to assess the specific changes in interregional connectivity patterns across the AM retrieval processes to understand network level mechanisms of AM retrieval and further test current theoretical accounts of dynamic AM retrieval processes. We predicted that dynamic connections would reflect two hypothesized memory processes, with initial processes reflecting memory-access related connections between regions such as the anterior hippocampal and ventrolateral PFC regions, and later processes reflecting elaboration-related connections between dorsolateral frontal working memory regions and parietal-occipital visual imagery regions. One week prior to fMRI scanning, fifteen healthy adult participants generated AMs using personally selected cue words. During scanning, participants were cued to retrieve the AMs. We used a moving-window functional connectivity analysis and graph theoretic measures to examine dynamic changes in the strength and centrality of connectivity among regions involved in AM retrieval. Consistent with predictions, early, access-related processing primarily involved a ventral frontal to temporal-parietal network associated with strategic search and initial reactivation of specific episodic memory traces. In addition, neural network connectivity during later retrieval processes was associated with strong connections between occipital-parietal regions and dorsal fronto-parietal regions associated with mental imagery, reliving, and working memory processes. Taken together, these current findings help refine and extend dynamic neural processing models of AM retrieval by providing evidence of the specific connections throughout the brain that change in their synchrony with one another as processing progresses from access of specific event memories to elaborative reliving of the past event. Highlights: AM retrieval involves dynamic changes in neural connectivity and network topology. Fronto-temporal-parietal networks are involved in early, access-related processing. Later, elaboration-related processing initially recruits occipital-parietal networks. Dorsal fronto-parietal connectivity persisted throughout the later elaboration periods. These findings extend and refine current theories of dynamic AM retrieval.